Consuelo Jimenez Underwood : art, weaving, vision - Pérez, Laura Elisa; Leimer, Ann (Duke University Press, 2022)
"Consuelo Jiménez Underwood, edited by art historians Laura E. Pérez and Ann Marie Leimer, focuses on Jiménez Underwood's weaving practice. The contributors explore themes of Chicana identity, nationalism, feminism, migration, and Indigenous philosophies in relation to Jiménez Underwood's art. The anthology is organized in three sections: "Spinning - Making Thread" provides introductory essays to Jiménez Underwood's work; "Weaving - Hand Work" provides art historical and visual cultural studies scholarship on the artist's work; and "Off the Loom - Into the World" examines Jiménez Underwood's role as a teacher"--